Inequivalent projections of some D-optimal designs - Evangelaras H.; Koukouvinos C. (Utilitas Mathematica, 2004)
Screening designs are useful for situations where a large number of factors (q) is examined but only few (k) of these are expected to be important. It is of practical interest for a given k to know all the inequivalent projections of the design into the k dimensions. In this paper we have found all the inequivalent projections of a number of designs in the class of n ≡ 1(mod4), n ≡ 2(mod4) and n ≡ 3(mod4) into k = 3, 4, 5 and 6 factors and we have also studied the geometric properties of these designs.